THE INTEGRATION OF COMPUTATIONAL CHEMISTRY TO SUPPORT INTERACTIVE LEARNING MEDIA FOR SENIOR HIGHSCHOOL: AN INNOVATIVE STRATEGY TO IMPLEMENT ‘KURIKULUM MERDEKA’ - Haq, Kautsar Ul; Kristanti, Alfinda Novi; Suwito, Hery; Aminah, Nanik Siti; Rusdipoetra, R. Aryabraga; Alfian, Fariz Rizky; Asyura, Syarifah (Universitas Airlangga, 2024)
Simulation or chemical modeling with computers is a major topic in computational chemistry. This subject is not covered in high school material, however, this method can be applied to support a more interactive learning process. Computational chemistry can be used as a virtual teaching aid and can also be used to help explain or predict chemical reactivity. The aim of this Community Service is to improve teachers' understanding of computational chemistry, both in theory and practice, according to the curriculum. The training activities were conducted using two methods: Lectures and practical sessions. Avogadro 1.2.0 and MOPAC2016 software were used for this training. The outcome of this program were evaluated using quantitative and qualitative analysis. The sustainability of the program was analyzed from the assignments regarding the plan to integrate the material provided into the learning process at schools. Based on the evaluation results, participants felt that the training they had received met their teaching needs. After participating in this training, the participants had various ideas for integrating computational chemistry into learning activities.